2016
DOI: 10.1556/2060.103.2016.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Muscle plasticity related to changes in tubulin and αB-crystallin levels induced by eccentric contraction in rat skeletal muscles

Abstract: We used the model of eccentric contraction of the hindlimb muscle by Ochi et al. to examine the role of eccentric contraction in muscle plasticity. This model aims to focus on stimulated skeletal muscle responses by measuring tissue weights and tracing the quantities of αB-crystallin and tubulin. The medial gastrocnemius muscle (GCM) responded to electrically induced eccentric contraction (EIEC) with significant increases in tissue weight (p < 0.01) and the ratio of tissue weight to body weight (p < 0.05); how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…(1) We pinpointed 21 relevant severely selected articles that include logistic regression, ROC curve analysis, linear regression, and voluntary categorizations to 6 BioMed Research International produce optimized cutoff points of physical fitness profiles (2) We continuously traced ideal cutoff threshold values from our reserved elderly human DB and found that individuals aged from 75 years for men and 70 years for women are within the specifically transitional age period for muscle mass (p < 0:01), which reflects the need for physical function tests in both genders (p < 0:01)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) We pinpointed 21 relevant severely selected articles that include logistic regression, ROC curve analysis, linear regression, and voluntary categorizations to 6 BioMed Research International produce optimized cutoff points of physical fitness profiles (2) We continuously traced ideal cutoff threshold values from our reserved elderly human DB and found that individuals aged from 75 years for men and 70 years for women are within the specifically transitional age period for muscle mass (p < 0:01), which reflects the need for physical function tests in both genders (p < 0:01)…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is a progressive deterioration of the loss of muscular mass and strength during aging [1,2]. Sarcopenia is significantly associated with declining physical activities, which induces a lower level of quality of life that eventually contributes to death.…”
Section: Introductionmentioning
confidence: 99%
“…The different ratios of the muscle types may be related to the heterogeneous expression of specific genes ( Cohen et al, 2015 ). The gastrocnemius muscle, considered in this study, is a fast-type skeletal muscle and consists of a balanced ratio of fast (78%∼95%) and slow (5%∼22%) fibers ( Jee et al, 2009 ; Jee et al, 2016b ). Such muscle is chosen to offset the possibility of having one-sided muscle fibers, which may influence gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, factors on both micro-and macroscales, including mechanical force, hormones, neurotransmitters, chemicals, nutrition and the process of aging, can influence the adaptability of the muscle as a whole [1][2][3][4]. Specifically, the extent of mechanical loading appears to be an important factor in the plasticity of muscle fibres [5]. To study the effect of unloading or inactivation of muscles on the plasticity of muscle fibres, researchers have reduced mechanical loading using the hindlimb suspension model, bed rest and spaceflight [6][7][8].…”
Section: Introductionmentioning
confidence: 99%